Bradysomnia in Parkinson's disease. Issue 2 (February 2016) - Imbach, Lukas L.; Sommerauer, Michael; Poryazova, Rositsa; Werth, Esther; Valko, Philipp O.; Scammell, Thomas E.; Baumann, Christian R.
Highlights: State space analysis enables quantitative assessment of the dynamics of sleep–wake behavior. Dynamical aspects of sleep/wake behavior are significantly impaired in Parkinson's patients. We suggest Bradysomnia as a novel potential biomarker for Parkinson's disease. Abstract: Objective: Polysomnography studies in Parkinson's disease (PD) patients show altered sleep microstructure with decreased level of arousability, indicating impaired sleep–wake dynamics in PD. The aim of this study was to investigate dynamical aspects of sleep EEG in PD as compared to healthy controls. Methods: In this retrospective, controlled study, we applied a previously established mathematical model of sleep EEG analysis (state space model) to PD patients and age- and gender-matched healthy volunteers ( N  = 64). Dynamical aspects of sleep were quantified by measuring the spectral variability of the sleep EEG (by means of state space velocity). Results: State space analysis revealed preserved global sleep–wake architecture in PD patients, but the velocity of sleep stage transitions was significantly reduced as compared to healthy controls. Correlation analysis revealed a strong association of state space velocity with arousal scores and daily dopamine agonist intake. Conclusions: Quantitative analysis of spectral sleep EEG variability (state space velocity) revealed reduced sleep–wake dynamics in PD patients as compared to control subjects. Significance: We propose state space velocity as an objective and quantitative measure for altered sleep microstructure and as a potential biomarker of sleep alterations in PD, not accessible by conventional sleep analysis.